2023
DOI: 10.3390/w15162897
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Influence on Compacted Snow Hardness by Density, Temperature and Punch Head Velocity

Abstract: The density, temperature, and punch head velocity are dominant factors to the variation of the compacted snow hardness measured by penetrometers. This effect is essential to the construction and operation of compacted snow roads. The Improved Motor-driven Snow Penetrometers (IMSP) are utilized in this research to control the penetration speed and measure the true cone hardness during snow penetration. This study employs a multi-method approach combining orthogonal experiments and the Support Vector Regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Some field penetration tests have become popular in recent years. Zhao et al [43] used an Improved Motor-driven Snow Penetrometer to measure the hardness of seasonal snow in Northeast China. The influence of different variables on snow hardness was analyzed using orthogonal tests.…”
Section: Viscosity Coefficientmentioning
confidence: 99%
“…Some field penetration tests have become popular in recent years. Zhao et al [43] used an Improved Motor-driven Snow Penetrometer to measure the hardness of seasonal snow in Northeast China. The influence of different variables on snow hardness was analyzed using orthogonal tests.…”
Section: Viscosity Coefficientmentioning
confidence: 99%
“…The deformation of the ice matrix mainly led to a reduction of the pore space and an increase in coordination number, while metamorphism mainly affected the grain and bond sizes. Zhao et al [22] found that density is positively correlated with the hardness of compacted snow, and its sensitivity and significance to the compacted snow hardness are the greatest. During the winter of 2007-2008, Arakawa et al [23] measured the specific surface area per unit snow volume and intrinsic permeability of naturally deposited dry snow in Hokkaido Prefecture, Japan, and found that the correlation between specific surface area per unit mass and intrinsic permeability could be used to clearly distinguish the snow types.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal characteristics and mechanical indices of snow are crucial parameters to be considered in cold-region science and engineering. The process of how snow evolves will undoubtedly be significantly impacted by changing climate conditions as global warming progresses [4,5], requiring a careful examination of snow mechanics and snow hazard issues [6][7][8][9][10]. In the future, a crucial strategy for dealing with snow science and snow risks will be to link the microstructure and apparent physical properties of snow.…”
Section: Introductionmentioning
confidence: 99%